Spatial Distribution of Greenland Shark Somniosus microcephalus (Bloch & Schneider, 1801) Life Stages Across the Northern North Atlantic - Julius Nielsen; Jørgen Schou Christiansen; Kim Præbel; Peter Rask Møller; Brynn Devine; Klara Jakobsdóttir; Nicolas Straube; Adriana Nogueira; Margaret Treble; Kevin Hedges; Sheila Atchison; Lise Helen Ofstad; et al. (Ecology and Evolution, 2025)
ABSTRACT Greenland sharks Somniosus microcephalus (Bloch & Schneider, 1801) are long‐lived and highly migratory animals distributed throughout deep and/or cold waters of the North Atlantic Ocean. Extensive bycatch in several demersal fisheries in the Arctic has raised conservation concerns for the species, of which surprisingly little is known about the spatial distribution in relation to their life history. In the current study, size, sex, and life stage composition of 1610 Greenland sharks were examined from 11 geographic regions across the northern North Atlantic Ocean. Subadult females dominated in most regions, and while adult females were scarce or absent in, for example, northern Arctic Canada and Svalbard, they dominated in southwest Greenland and Iceland. Furthermore, in southern Arctic Canada, northwestern Greenland, and southeastern Greenland, adult females were more commonly encountered in offshore waters than inshore. Depth (25 m to 1375 m) had little effect on the spatial distribution irrespective of length and life stage, whereas water temperatures (−1.54°C to 10.9°C) conclusively showed that adult females preferred warm water (> 4°C). Large juveniles were encountered in most regions but dominated in Skagerrak and in offshore southern Arctic Canada. Small juveniles and neonates were encountered with only five and zero records, respectively, combined for all analyzed regions. In an additional effort to identify these rare, small‐sized specimens, scrutinization of museum collections and databases of scientific institutions disclosed a cluster of ten neonates (total length < 60 cm) and two small juveniles (total length 60‐89 cm) along the mid‐Atlantic Ridge and the Irminger Sea. This finding is unique and suggests the location of a potential Greenland shark pupping ground on or in the vicinity of the mid‐Atlantic Ridge and Irminger Sea. All combined, this study provides new insights into the life history of the Greenland shark, which will aid the development of targeted conservation measures.